Leadership practices and sustained lesson study. Issue 3 (3rd July 2022) - van den Boom-Muilenburg, Selia Neeske; de Vries, Siebrich; van Veen, Klaas; Poortman, Cindy; Schildkamp, Kim
ABSTRACT: Background: The continual improvement of teaching and learning is vital for schools in order to meet the rapid changes in the world around us. Lesson study is considered a valuable professional development approach in that regard. It is focused on teachers collaboratively studying live classroom lessons. Sustaining lesson study, by making its core components part of the school's organisational routines, can help schools continually and systematically to improve student learning and teaching. However, despite the value of this approach, sustaining lesson study turns out to be complex. Leadership seems to play a crucial role therein, but the question is: how? Purpose: The study aimed to gain in-depth insight into what leadership looks like in schools that sustained lesson study. Method: A case study design was used to investigate leadership in two secondary schools. We conducted over 300 hours of observations through immersion within practice, collected school policy documents, and interviewed the school leadership. Data were analysed qualitatively. Findings: The analysis identified that both schools carried out various leadership practices for sustained lesson study. For leadership at schools that aim for sustained lesson study, it seems important to schedule lesson study, to be available, to have knowledge about lesson study and to appoint a lesson study coordinator. Whether and how leadership practices were carried out seemed to depend on the school's context – for instance, by the policy reasons for working with lesson study. As such, it is important to examine the school and its leadership in context when considering sustainability. Conclusion: Through immersion within practice, specific and real-life examples of leadership were identified. This study's insights could help school leadership to sustain lesson study in their schools.